The Guaranteed Cost Control of Uncertain Nonlinear Discrete Systems - FAN Li-ying; SONG Jing-jing; ZHANG Jia-ning; HONG Gang (Journal of Harbin University of Science and Technology)
In this paper, the problem of guaranteed cost control for a class of uncertain nonlinear discrete systems with state and input delay is studied. By applying Lyapunov stability theory and linear matrix inequality approach, sufficient conditions for the existence of state feedback controller are obtained to guarantee that the asymptotical stability of the close loop system and the quadratic performance index less a certain bound for all admissible uncertainties,t herefore, guaranteed cost problem solving. Finally, the effectiveness of the proposed method can be illustrated by the simulation example.